2018
DOI: 10.1002/ncp.10182
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Adaptation of the Spanish Version of the STRONGkids Nutrition Screening Tool

Abstract: The SV of the MST showed good reliability and feasibility. The validity is moderate, and the MST could be considered a useful resource for early detection of malnutrition risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
1
9
0
3
Order By: Relevance
“…Twenty‐eight studies evaluated the concurrent validity of one or more NS pediatric tools 8,9,30,32,34–36,39–41,45,48,51,52,55–59,61,63,64,66–71 . The following reference standards were used in these studies: anthropometric indexes, 7,35,36,39–41,48,51,52,55,56,59,61,63,68,70,71 complete nutrition status evaluation, 8,28,32,64,67 the SGNAped, 35,36,45,56,69 the consensus in malnutrition diagnosis from the Academy of Nutrition and Dietetics (AND)/American Society for Parenteral and Enteral Nutrition (ASPEN), 30,36 and dual‐energy x‐ray absorptiometry 68 . The diagnostic accuracy data are presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐eight studies evaluated the concurrent validity of one or more NS pediatric tools 8,9,30,32,34–36,39–41,45,48,51,52,55–59,61,63,64,66–71 . The following reference standards were used in these studies: anthropometric indexes, 7,35,36,39–41,48,51,52,55,56,59,61,63,68,70,71 complete nutrition status evaluation, 8,28,32,64,67 the SGNAped, 35,36,45,56,69 the consensus in malnutrition diagnosis from the Academy of Nutrition and Dietetics (AND)/American Society for Parenteral and Enteral Nutrition (ASPEN), 30,36 and dual‐energy x‐ray absorptiometry 68 . The diagnostic accuracy data are presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…13 Several hospitals also used STRONGkids that has been modified based on the hospital specification. 15 Alarm Malnutrition needs some modification and improvement in the cut off value of MaR so it can be used as a screening tool accordance with the characteristics of the child. Besides being proven as good, STRONGkids is also easy to use, therefore it can help the nurses in detecting the risks for HaM in children.…”
Section: Discussionmentioning
confidence: 99%
“…65 In this context, STRONGkids stands out for being a simple, quick, and low-cost method. Because it does not require anthropometric measures or equipment expenses, and because of it its speed of application (on average, 3 minutes), 66 resources can be concentrated on higherpriority actions. The reliability of STRONGkids has been demonstrated even when applied by different professionals 63,67 and by nonspecialized staff, 38 which also contributes to its feasibility in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…It was a single-center study, so the results may not be extrapolated to other populations. In addition, the variation of dietitians applying STRONGkids should be mentioned, although previous studies 38,63,[66][67][68] have confirmed the method's interrater reproducibility.…”
Section: Discussionmentioning
confidence: 99%